CLE peptide signaling in plant-microbe interactions - Nakagami, Satoru; Kajiwara, Taiki; Tsuda, Kenichi; Sawa, Shinichiro (Frontiers in Plant Science, 2024)
Cell-cell communication is essential for both unicellular and multicellular organisms. Secreted peptides that act as diffusive ligands are utilized by eukaryotic organisms to transduce information between cells to coordinate developmental and physiological processes. In plants, The CLAVATA3/EMBRYO SURROUNDING REGION-RELATED (CLE) genes encode a family of secreted small peptides which play pivotal roles in stem cell homeostasis in various types of meristems. Accumulated evidence has revealed that CLE peptides mediate trans-kingdom interactions between plants and microbes, including pathogens and symbionts. This review highlights the emerging roles of CLE peptide signaling in plant-microbe interactions, focusing on their involvement in nodulation, immunity, and symbiosis with arbuscular mycorrhizal fungi. Understanding these interactions provides insights into the sophisticated regulatory networks to balance plant growth and defense, enhancing our knowledge of plant biology and potential agricultural applications.